THE IMPLEMENTATION OF CHARACTER EDUCATION IN "SENI KARAWITAN (SEKAR)" EXTRACURRICULAR ACTIVITIES IN SD NEGERI KAUMAN - Fitriani, Oktavia; Isnaini, Isnaini; Hasanah, Uswatun (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
This research is aimed to describe the implementation of character education in the "Seni Karawitan (Sekar)" extracurricular activity in Kauman State Elementary School. The study used a descriptive qualitative method. This research was conducted by using an observation technique. The students who joined the Seni Karawitan extracurricular activity were observed. Character education is implemented in that activity. The steps in this research include finding the problem, formulating the hypothesis, collecting the relevant data, analyzing the data, and testing the hypothesis. The results of this study show the character education is implemented in the Seni Karawitan extracurricular activity as an effort to grow the character in the young age. The implementation is done through the attitudes and actions that have to be performed by the students when they play gamelan and sang Javanese songs. Seni Karawitan has the values of togetherness, leadership, patience, responsibility, politeness, loving the culture, religiousity, gentleness, honesty, discipline, model, concentration, tolerance, happiness, and education. The values reflect the characters that have to be preserved and respected in the daily life. The students of Kauman State Elementary School are more focused on some values, namely togetherness, patience, leadership, politeness, loving the culture, and responsibility.